The curvilinear relationship between within-person creative self-efficacy and individual creative performance: the moderating role of approach/avoidance motivations. Issue 9 (13th April 2020) - Li, Ci-Rong; Yang, Yanyu; Lin, Chen-Ju; Xu, Ying
Abstract : Purpose: This research adopts a dynamic self-regulation framework to test whether there is a curvilinear relationship between creative self-efficacy and individual creative performance at the within-person level. Furthermore, to establish a boundary condition of the predicted relationship, the authors build a cross-level model and examine how approach motivation and avoidance motivation moderate the complex relationship between creative self-efficacy and individual creative performance. Design/methodology/approach: To obtain results from a within-person analysis, the authors collect multi-source data from 125 technicians who provided monthly reports over an 8-month period. Findings: The authors find evidence of an inverted U-shaped relationship between creative self-efficacy and individual creative performance at the within-person level and differential moderating effects of approach/avoidance motivations. Originality/value: This study is one of the first to challenge the assumption that creative self-efficacy always has a positive linear relationship with creativity. It provides a more complete view of the complex pattern between creative self-efficacy and creativity at the within-person level.